En route to a unified model for photo-electrochemical reactor optimisation. I - Photocurrent and H2 yield predictions12. Issue 43 (25th October 2017) - Bedoya-Lora, Franky E.; Hankin, Anna; Kelsall, Geoff H.
Abstract : A photo-electrochemical cell model was developed accounting for photon flux, electron–hole recombination rates, gas desorption, bubble formation and cross-over losses. Abstract : A semi-empirical model was developed for the prediction of photocurrent densities and implemented to predict the performance of a photo-electrochemical reactor for water splitting in alkaline solutions, using Sn IV -doped α-Fe2 O3 photo-anodes produced by spray pyrolysis. Photo-anodes annealed at different temperatures were characterised using photo-electrochemical impedance spectroscopy, cyclic voltammetry in the presence and absence of a hole scavenger and also the open circuit potential under high intensity illumination. Mott–Schottky analysis was used cautiously to estimate the charge carrier concentration and the flat band potential. In addition to overpotential/current distribution and ohmic potential losses, the model also accounts for absorbed photon flux, surface and bulk electron–hole recombination rates, gas desorption, bubble formation and (H2 –O2 ) cross-over losses. This allows the model to estimate the total yield of hydrogen, charge and gas collection efficiencies. A methodology is presented here in order to evaluate the parameters required to assess the performance of a photo-electrochemical reactor in 1D and 2D geometries. The importance of taking into account bubble generation and gas desorption is discussed, together with the difficulties of measuring charge carrier concentration and electron–hole recombination in the bulk of the semiconductor, which are of major importance in the prediction of photocurrent densities.